2016
DOI: 10.1128/jcm.00834-16
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Patterns of Brachyspira Species Isolated from Swine Herds in the United States

Abstract: Outbreaks of swine dysentery, caused by Brachyspira hyodysenteriae and the recently discovered "Brachyspira hampsonii," have reoccurred in North American swine herds since the late 2000s. Additionally, multiple Brachyspira species have been increasingly isolated by North American diagnostic laboratories. In Europe, the reliance on antimicrobial therapy for control of swine dysentery has been followed by reports of antimicrobial resistance over time. The objectives of our study were to determine the antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
29
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 35 publications
(113 reference statements)
8
29
0
3
Order By: Relevance
“…For valnemulin, the results were similar to those previously reported (Karlsson et al 1999, 2002, Rohde et al 2004, Hidalgo et al 2009, 2011, Zmudzki et al 2012, Alvarez et al 2013, Mirajkar & Gebhart 2013. The MIC50 results for tiamulin were higher than those published elsewhere, but the MIC90 was similar to the results obtained by Rohde et al (2004), Hidalgo et al (2011) and by Alvarez et al (2013).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…For valnemulin, the results were similar to those previously reported (Karlsson et al 1999, 2002, Rohde et al 2004, Hidalgo et al 2009, 2011, Zmudzki et al 2012, Alvarez et al 2013, Mirajkar & Gebhart 2013. The MIC50 results for tiamulin were higher than those published elsewhere, but the MIC90 was similar to the results obtained by Rohde et al (2004), Hidalgo et al (2011) and by Alvarez et al (2013).…”
Section: Discussionsupporting
confidence: 90%
“…Hidalgo et al (2011) identified a mutation in the 23S gene at position 2059 associated with resistance to tylvalosin. For lincomycin, the MIC50 was higher compared with that reported in the literature (Karlsson et al 1999, Karlsson et al 2002, Karlsson et al 2003, Rohde et al 2004, Hidalgo et al 2011, Zmudzki et al 2012, Mirajkar & Gebhart 2013, however, the MIC 90 was similar to those obtained by Hidalgo et al (2009) and Alvarez et al (2013).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations